Intensification to injectable therapy in type 2 diabetes: mixed methods study (protocol). - De Lusignan, S; Hinton, W; Konstantara, E; Munro, N; Whyte, M; Mount, J; Feher, M (BioMed Central, 2019)
BACKGROUND: In the UK, type 2 diabetes mellitus (T2D) is largely managed in primary care. Delay in the intensification to injectable therapy, a form of clinical inertia, is associated with worse glycaemic control. UK general practice is highly computerised, with care being recorded on computerised medical record systems; this allows for quantitative analysis of clinical care but not of the underpinning decision-making process. The aim of this study is to investigate perceptions of patients and clinicians in primary care on the initiation of injectable therapies in T2D, and the context within which those decisions are made. METHODS: This is a mixed methods study, taking a "realist evaluation" approach. The qualitative components comprise focus groups, interviews, and video recordings of simulated surgeries; the quantitative analysis: an overview of participating practices, elements of the video recording, and an online survey. We will recruit primary care clinicians (general practitioners and nurses) and patients from a representative sample of practices within the Royal College of General Practitioners (RCGP) Research and Surveillance Centre (RSC) network. Participants will be patients with T2D, and primary care clinicians. Focus groups and semi-structured interviews will be recorded, transcribed verbatim and analysed using Framework Analysis. The simulated surgeries will include cases that might be escalated to injectable therapy. The consultation will be reviewed using the Calgary-Cambridge model to assess communication and determination of adherence to national prescribing guidelines. We will conduct multi-channel video recording including screen capture, clinician and patient facial expressions, wide angle view of the consultation, and the computerised medical record screen. This allows annotation and qualitative analysis of the video recordings, and statistical analyses for the quantitative data. We will also conduct an online survey of primary care clinicians' attitudes to, and perceptions of, initiation of injectable therapies, which will be analysed using summary statistics. DISCUSSION: Results aim to provide a detailed insight into the dynamic two-way decision-making process underpinning use of injectable therapy for T2D. The study will provide insights into clinical practice and enable the development of training, interventions and guidelines that may facilitate, where appropriate, the intensification to injectable therapy.